YOUNG JU’S HYBRID IDENTITY IN AN NA’S A STEP FROM HEAVEN - M. Fadlil Abdillah; Eko Suwargono; Irana Astutiningsih (Fakultas Ilmu Budaya Universitas Jember, 2017)
AbstractThis study discusses hybrid identity problem experienced by the main character, Young Ju, in A Step from Heaven. As a diasporic subject, she has to face some problems related to her identity. Her effort to survive among the differences of two different cultures (South Korea/eastern and America/western) is the main problem this study. Besides, the violence of her father becomes a barrier to her adaptation process in the new environment. For that reason, the problems are analyzed in this study using theory of hybridity by Homi K. Bhabha. The result of this study shows that to survive in a place with many differences especially it has relation to identity and culture, Young Ju needs to adopt some cultures that consider can give advantage in order to survive without losing the old culture. Then, this process leads her to be hybrid subject. By having the hybrid identity, it means that her hard work to accustom with the host society is running smoothly.